Analisis Konsep Islam Tradisi Upah Buruh Tani - Yuni Hidayatun Nisa; M. Khairul Hadi Al-Asy’ari (Jurnal Istiqro, 2019)
This paper starts from the phenomenon that 80% of the common people are farmers. Ironically, farmers here as farm workers 90% and 10% are land owners. The landowners (musta'jir) and farm workers (ajir) have good relationships because of the attachment of mutual need. But the problems that occur are that the culture of the wage system is still lacking. The first focus of the problem is what is the concept of wages applied in the village of Mandigu? The second is how the concept of wages is liberal and its relevance to the Islamic concept? The purpose of this study is to find out what are the concepts of wages applied and whether they are relevant to the Islamic concept. This research uses field research that is plunge or descend directly to the object of research to obtain data that the researcher needs. The object of this research is mandarin hamlet. The subjects studied were land owners, farm laborers and village officials. The results of this study reveal that there are four concepts of wages applied but people tend to choose the concept of concrete because the concrete system has been derived from ancestors and in terms of acceptable benefits between the two parties.